Servqual Model Approach in Measuring Students’ Satisfaction in The Faculty of Dakwah and Communication Science - Ricka, Ricka Handayani; Eviyanti, Yuli; Arnada, Feby (Journal of Islamic Management, 2024)
The objective of this research is to measure the level of students' satisfaction through the SERVQUAL model approach. The model consists of five dimensions: tangibles, assurance, reliability, responsiveness, and empathy. The research was conducted in the Faculty of Da'wah and Communication Sciences at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The data for the current research was collected by distributing questionnaires to 235 students and analyzed using Structural Equation Modeling (SEM) with Smart PLS. After thoroughly and precisely assessing the data, it was discovered that all elements of the SERVQUAL model, namely tangibles, assurance, dependability, responsiveness, and empathy, had a positive and significant effect on students’ satisfaction. This research is expected to be applied as a basis for developing Standard Operating Procedures (SOP) to provide exceptional service in the primary activities and functions of work units at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan and other educational institutions